Evolution of Nanotechnology in Delivering Drugs to Eyes, Skin and Wounds via Topical Route - Pratheeksha Koppa Raghu; Kuldeep K. Bansal; Pradip Thakor; Valamla Bhavana; Jitender Madan; Jessica M. Rosenholm; Neelesh Kumar Mehra (MDPI AG, 2020)
The topical route is the most preferred one for administering drugs to eyes, skin and wounds for reaching enhanced efficacy and to improve patient compliance. Topical administration of drugs via conventional dosage forms such as solutions, creams and so forth to the eyes is associated with very low bioavailability (less than 5%) and hence, we cannot rely on these for delivering drugs to eyes more efficiently. An intravitreal injection is another popular drug delivery regime but is associated with complications like intravitreal hemorrhage, retinal detachment, endophthalmitis, and cataracts. The skin has a complex structure that serves as numerous physiological barriers to the entry of exogenous substances. Drug localization is an important aspect of some dermal diseases and requires directed delivery of the active substance to the diseased cells, which is challenging with current approaches. Existing therapies used for wound healing are costly, and they involve long-lasting treatments with 70% chance of recurrence of ulcers. Nanotechnology is a novel and highly potential technology for designing formulations that would improve the efficiency of delivering drugs via the topical route. This review involves a discussion about how nanotechnology-driven drug delivery systems have evolved, and their potential in overcoming the natural barriers for delivering drugs to eyes, skin and wounds.